2020
DOI: 10.3390/ijerph17165921
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Depressive Symptoms—A Longitudinal Study from Early to Late Adolescence

Abstract: An increasing number of studies have addressed how adolescents’ social media use is associated with depressive symptoms. However, few studies have examined whether these links occur longitudinally across adolescence when examined at the individual level of development. This study investigated the within-person effects between active social media use and depressive symptoms using a five-wave longitudinal dataset gathered from 2891 Finnish adolescents (42.7% male, age range 13–19 years). Sensitivity analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 72 publications
0
41
2
2
Order By: Relevance
“…One must not shut out the possibility of a sort of dynamic of escapism either (Calleja, 2010; Hirschman, 1982), as in some cases the individuals in this study brought up difficult socioemotional situations (breakup or tragic death of a relative), not to mention the apparently low sociometric status of some (indicating loneliness), that might affect the intensity of their SDP. There is, in fact, recent evidence suggesting that depressive symptoms might lead to increased social media use but not the other way round (Puukko, Hietajärvi, Maksniemi, Alho, & Salmela‐Aro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One must not shut out the possibility of a sort of dynamic of escapism either (Calleja, 2010; Hirschman, 1982), as in some cases the individuals in this study brought up difficult socioemotional situations (breakup or tragic death of a relative), not to mention the apparently low sociometric status of some (indicating loneliness), that might affect the intensity of their SDP. There is, in fact, recent evidence suggesting that depressive symptoms might lead to increased social media use but not the other way round (Puukko, Hietajärvi, Maksniemi, Alho, & Salmela‐Aro, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Raudsepp and Kais's ( 35 ) 2-year study of adolescent girls revealed that baseline levels of depressive symptoms predicted problematic social media use, whereas prior social media use did not predict depressive symptoms. Examining the within-person effects of depressive symptoms on increased social media use over 6 years during early and late adolescence, Puukko et al ( 36 ) found that depressive symptoms predicted increases in social media use for both boys and girls. Conversely, social media use was not found to predict depressive symptoms.…”
Section: Evidence For Reverse Causality In the Relationship Between Social Media And Depressive Symptomsmentioning
confidence: 99%
“…In addition to the diversification of study designs, another notable development in (social) media effects research is that within-person methods of analysis are gaining prominence, for example as applied in random-intercept cross-lagged panel models (Puukko et al, 2020) and multi-level modeling (Beyens et al, 2020). Studies that focus on withinperson effects investigate to what extent ASMU and PSMU lead to increases (or decreases) in well-being within a person compared to this person's average well-being (Nesselroade, 1991, p. 229).…”
Section: Different Designs Different Effectsmentioning
confidence: 99%
“…During the coding, we discovered that several operationalizations consisted of a mix of public and private items to measure ASMU and PSMU (Aalbers et al, 2019;Beyens et al, 2020;Puukko et al, 2020;Thorisdottir et al, 2019;Yang, 2020). In subsequent sections, we investigated these studies as a separate category, named mixed ASMU or PSMU.…”
Section: Public Versus Private Asmu and Psmumentioning
confidence: 99%
See 1 more Smart Citation